Direct growth of crystalline triazine-based graphdiyne using surface-assisted deprotection–polymerisation. Issue 38 (31st August 2021) - Kulkarni, Ranjit; Huang, Jieyang; Trunk, Matthias; Burmeister, David; Amsalem, Patrick; Müller, Johannes; Martin, Andréa; Koch, Norbert; Kass, Dustin; Bojdys, Michael J.
Abstract : We present a one-pot deprotection/polymerisation protocol for the synthesis of crystalline graphdiynes on top of a copper surface starting with stable trimethylsilylated alkyne monomers. Abstract : Graphdiyne polymers have interesting electronic properties due to their π-conjugated structure and modular composition. Most of the known synthetic pathways for graphdiyne polymers yield amorphous solids because the irreversible formation of carbon–carbon bonds proceeds under kinetic control and because of defects introduced by the inherent chemical lability of terminal alkyne bonds in the monomers. Here, we present a one-pot surface-assisted deprotection/polymerisation protocol for the synthesis of crystalline graphdiynes over a copper surface starting with stable trimethylsilylated alkyne monomers. In comparison to conventional polymerisation protocols, our method yields large-area crystalline thin graphdiyne films and, at the same time, minimises detrimental effects on the monomers like oxidation or cyclotrimerisation side reactions typically associated with terminal alkynes. A detailed study of the reaction mechanism reveals that the deprotection and polymerisation of the monomer is promoted by Cu(ii ) oxide/hydroxide species on the as-received copper surface. These findings pave the way for the scalable synthesis of crystalline graphdiyne-based materials as cohesive thin films.